Dispensasi Nikah Setelah Berlakunya Undang-Undang Nomor 16 Tahun 2019 Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 Perspektif Maqashid Syariah - Muzaiyanah Muzaiyanah; Anies Shahita Aulia Arafah (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
According to Article 7 paragraph (1) Law no. 16 years 2019, the marriageable age for marriage of men and women is 19 years. However, if someone is under 19 years of age have not been allowed to enter into a marriage and are considered illegitimate in the state. However, if there is an emergency due to pregnancy, fear of adultery, shame because not yet married, fearing things that are prohibited by religion, you can apply for a marriage dispensation. This study uses a qualitative approach with a literature review method. Aiming to find out the application of law No. 16 of 2019 from the perspective of Maqashid Syariah. The result of the research explains that the Panel of Judges considers and makes the fairest decision to decide whether it is worth giving a dispensation. Based on the first Maqashid Syariah, dharuriyah is used to avoid adultery and protect offspring born from pregnancy after marriage. Second, the hajiyyat considers suspicion of responsibility, for example a spouse already has a job and is physically and mentally ready. Third, parents' tahsiniyat guarantees that they are responsible for the child's economic, social, health and educational problems.